A parent‐based intervention to promote healthy eating and active behaviours in pre‐school children: evaluation of the MEND 2–4 randomized controlled trial. Issue 1 (27th February 2015) - Skouteris, H.; Hill, B.; McCabe, M.; Swinburn, B.; Busija, L.
Summary: Background: There is a paucity of studies evaluating targeted obesity prevention interventions in pre‐school children. Objectives: We conducted a randomized controlled trial to evaluate the efficacy of a parent‐based obesity prevention intervention for pre‐schoolers – MEND (Mind, Exercise, Nutrition … Do It!) 2–4 on child diet, eating habits, physical activity/sedentary behaviours, and body mass index (BMI). Methods: Parent–child dyads attended 10 weekly 90‐min workshops relating to nutrition, physical activity and behaviours, including guided active play and healthy snack time. Assessments were conducted at baseline, immediately post‐intervention, and 6 and 12 months post‐intervention; child intake of vegetables, fruit, beverages, processed snack foods, fussiness, satiety responsiveness, physical activity, sedentary behaviour and neophobia were assessed via parent proxy report. Parent and child height and weight were measured. Results: Two hundred one parent–child dyads were randomized to intervention ( n  = 104) and control ( n  = 97). Baseline mean child age was 2.7 (standard deviation [SD] 0.6) years, and child BMI‐for‐age z ‐score (World Health Organization) was 0.66 (SD 0.88). We found significant positive group effects for vegetable ( P  = 0.01) and snack food ( P  = 0.03) intake, and satiety responsiveness ( P  = 0.047) immediately post‐intervention. At 12 months follow‐up, intervention children exhibited less neophobia ( P  = 0.03) than controls. Conclusion: Future research should focus on additional strategies to support parents to continue positive behaviour change. ACTRN12610000200088.